Analisis Kinerja Manajemen Keuangan Daerah melalui Pendapatan Asli Daerah (PAD) Kabupaten Klaten - Rahmawati Riantisari; Alfiati Nurrokhmini; Noviadry Nur Tamtama (Lembaga Penelitian dan Pendidikan (LPP) Kalibra, 2026)
This study is motivated by the importance of regional fiscal independence, which is reflected in the ability of local governments to manage Regional Original Revenue (PAD). Klaten Regency has considerable economic potential; however, the contribution of PAD to total regional revenue remains relatively low. This study aims to analyze the development, structure, and management performance of PAD in Klaten Regency. The method used is a descriptive quantitative approach employing time series data from 2020 to 2024, analyzed using effectiveness, efficiency, and independence ratios. The results show that PAD in Klaten Regency tends to increase but remains fluctuating and therefore not yet stable. The structure of PAD has shifted from the dominance of other legitimate revenues toward local taxes and retributions, although this change has not been consistent. In terms of performance, PAD is considered effective as its realization consistently exceeds the target; however, it is not yet efficient because regional expenditures are significantly higher than PAD. In addition, the level of regional financial independence is still very low, indicating a high dependence on central government transfers. In conclusion, the increase in PAD has not been accompanied by optimal management quality. Therefore, efforts are needed to strengthen a more stable revenue structure, improve management efficiency, and reduce dependence on external revenue sources in order to enhance regional fiscal independence.